Evaluasi Implementasi Pelayanan Kesehatan Tradisional Di Puskesmas Sawit Kabupaten Boyolali, Jawa Tengah - Sri Mumpuni Yuniarsih; Rahajeng Win Martani; Nunung Hasanah (Jurnal Ventilator, 2023)
Traditional health services are expected to be implemented in health care facilities. Puskesmas had a traditional health clinic that has been running since 2019, but there is no evaluation on that program. This study aims to identify the implementation that has been carried out, in order to find out which aspects still need improvement. The research method used is descriptive qualitative research. Researchers collect data by interview, observation and secondary data. The results of the study show that traditional health services at the puskesmas have been implemented fairly well. In 2022 there were 20 visitors with the majority of visitors aged 31-45 years (50%), female (90%), all coming from the Javanese and Muslim religions. Meanwhile, the average number of visits was 1 time (55%) and 5% of visitors made 4 repeat visits. The most frequently treated complaints were dizziness/headaches (35%) and other pain complaints (45%). Treatment in traditional health polyclinics is provided with oral medication as much as 40% and 60% without drug administration. The traditional treatment given is acupressure (65%), cupping (15%) and a combination of both as much as 20%. Officers who provide traditional health services at the Palm Health Center are nurses with acupressure training. The implementation that has been carried out still requires various improvements in order to increase the number of patient visits. Further research is needed to find the right implementation model so that traditional health services at puskesmas are widely utilized by the community.